2003
DOI: 10.1097/00001756-200307180-00017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial map of frequency tuning-curve shapes in the mouse inferior colliculus

Abstract: Neurons in the central nucleus of the auditory midbrain inferior colliculus divide into four classes according to the shapes of their receptive fields. Neurons of two of these classes - sharply tuned, inhibition-dominated neurons of class II, and broadly tuned neurons of class III - show systematic gradients in their abundance on isofrequency contours. Sharp tuning is most prevalent in the center, broad tuning in the periphery of the ICC. This new map of tuning-curve shape adds to the six previously described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…An important challenge in understanding the organization of the IC is discovering what is represented over the surface of a frequency-band lamina, i.e., in the plane orthogonal to the tonotopic axis. Evidence exists for a shallow gradient in best frequency across the laminae (Langner and Schreiner,1988; Malmierca et al,2008; Merzenich and Reid,1974), and other stimulus features have also been reported to be mapped over their surface, including modulation frequency periodotopy (Langner and Schreiner,1988; Schreiner and Langner,1988), selectivity for rate of change of frequency (Ehret et al,2003; Hage and Ehret,2003), and unit threshold and bandwidth of frequency tuning (Schreiner and Langner,1988; for reviews see Ehret and Schreiner,2005; Rees and Langner,2005). The divergent pattern of connections we have observed could be a means by which the integration of responses across such parameter representations is affected.…”
Section: Discussionmentioning
confidence: 99%
“…An important challenge in understanding the organization of the IC is discovering what is represented over the surface of a frequency-band lamina, i.e., in the plane orthogonal to the tonotopic axis. Evidence exists for a shallow gradient in best frequency across the laminae (Langner and Schreiner,1988; Malmierca et al,2008; Merzenich and Reid,1974), and other stimulus features have also been reported to be mapped over their surface, including modulation frequency periodotopy (Langner and Schreiner,1988; Schreiner and Langner,1988), selectivity for rate of change of frequency (Ehret et al,2003; Hage and Ehret,2003), and unit threshold and bandwidth of frequency tuning (Schreiner and Langner,1988; for reviews see Ehret and Schreiner,2005; Rees and Langner,2005). The divergent pattern of connections we have observed could be a means by which the integration of responses across such parameter representations is affected.…”
Section: Discussionmentioning
confidence: 99%
“…3C and D). In the mouse IC, tuning curve shapes have been classified as broadly tuned on the low frequency side and sharply tuned on the high frequency side (class I), sharply tuned on both sides (class II), broadly tuned (classic V-shape, class III) or complexly tuned with multiple regions of excitation (class IV) (Egorova et al, 2001; Ehret et al, 2003). Class II and III tend to be most prevalent (~30 % each) (Egorova et al, 2001; Portfors et al, 2011).…”
Section: General Features Of Auditory Processing In Ic and Mldmentioning
confidence: 99%
“…Within the frequency laminae of the IC there exist secondary spatial gradients in response properties, including a gradient in the limited range of frequencies contained in a single lamina that is orthogonal to the main frequency axis in the IC (Schreiner and Langner 1997). In addition to a gradient in CFs, there are gradients in other types of response properties including the pattern of the spike train, the shape of the frequency tuning curve, selectivity for FM sweeps, or the degree to which binaural responsiveness is shaped by ipsilateral inhibition (Wenstrup et al 1985(Wenstrup et al ,1986Bruckner and Rubsamen 1995;Hage and Ehret 2003;Ehret et al 2003). Because we did not measure these response properties in the current study, we cannot evaluate whether fenfluramine selectively increases the latencies of these types of neurons, but these possibilities can be tested in the future.…”
Section: A Difference In the Effects Of Fenfluramine Versus Serotoninmentioning
confidence: 99%